Matrix-Associated Autologous Chondrocyte Implantation: A Clinical Follow-Up at 15 Years. (October 2016) - Gille, Justus; Behrens, Peter; Schulz, Arndt Peter; Oheim, Ralf; Kienast, Benjamin
Introduction: A prospective clinical investigation was carried out in order to clarify whether Matrix-associated autologous chondrocyte implantation (MACI) results in clinical improvement at long-term follow-up. Hypothesis: MACI will result in clinical improvement at long-term follow-up. Study Design: Case series; level of evidence, 4. Methods: Thirty-eight patients were treated with MACI. These patients were evaluated for up to a mean of 16 years (range 15-17 years) after the intervention. Three different scores (Lysholm-Gilquist score, International Cartilage Repair Society score, and Tegner score) formed the basis of this study. Overall, we were able to obtain valid preoperative and postoperative results from 18 (47%) of 38 patients. In 1 patient, both knees were treated. In 4 patients, an arthroplasty was implanted over the course of time; thus they were excluded from this case series. In conclusion, follow-up of 15 knees was performed in the recent series. Results: In subjective rating, 12 out of 14 patients (86%) rated the function of their knee as much better or better than before the index procedure. All numerical outcome scores showed significant improvement compared to the preoperative value (preoperative/postoperative at 5 years/postoperative at 15 years): Lysholm score 59.6 (±24.6)/78.6 (±21.5)/82.7 (±11.3), International Knee Documentation Committee score 50.6 (±22.7)/64.7 (±21.6)/69.7 (±18.7), Tegner score 3.0 (±2.2)/3.6 (±1.5)/5.2 (±1.7). Conclusion: The significantly improved results on 3 scores after 15 years suggest that MACI represents a suitable treatment of local cartilage defects in the knee.